Cuproptosis: a novel therapeutic mechanism in lung cancer - Cheng Luo; Xinhui Wu; Shipeng Zhang; Junwen Tan; Yuzhi Huo; Xinyue Zhang; Bo Ning; Yuanhang Ye; Fei Wang (Cancer Cell International, 2025)
Abstract Background Lung cancer, one of the most prevalent and deadly malignant tumors, is increasingly common globally in terms of both morbidity and mortality rates. Unlike pyroptosis and necroptosis, cuproptosis is a non-apoptotic programmed cell death process. Studies have demonstrated that cuproptosis is involved in the incidence, development, and metastasis of lung cancer. However, the mechanisms underlying cuproptosis in lung cancer remain to be fully elucidated. Purpose In this work, we primarily examine the most recent research on copper homeostasis, cuproptosis mechanisms, and the connection between lung cancer and cuproptosis. Methods A comprehensive literature search was conducted using the Web of Science, PubMed, and Google Scholar databases. The search strategy employed a combination of the keywords “cuproptosis” and “lung cancer.” The results encompassed publications from January 2020 to May 2025. This study aimed to gather research focusing on the relationship between lung cancer and cuproptosis, as well as the anticancer effects of drugs that induce cuproptosis. Results Our research indicates that lung cancer patients experience disruptions in copper ion homeostasis, as well as inhibition of cuproptosis, which points to a potentially effective therapeutic avenue through the induction of cuproptosis in lung cancer cells. This paper provides an overview of the mechanisms that highlight proteins associated with copper homeostasis and genes that play a role in cuproptosis in the lung cancer context. The modulation of proteins such as CTR1, ATOX1, FDX1, CCS, COX17, ATP7A, and ATP7B, in addition to LIPT1 and various long non-coding RNAs (AL691432.2, AC093010.2, AC107464.3, COLCA1, AC026471.3, LINC01833, and ITGB1-DT), along with genes such as DβH, LOXL2, SOD1, UBE2D1, and UBE2D3, can affect these mechanisms. These elements are vital for evaluating clinical interventions for lung cancer patients, predicting risks, and recognizing drug resistance. Moreover, we identified that pharmaceuticals facilitating copper ion transport (elesclomol and disulfiram), copper-chelating agents (DPEN, ATTM, and TETA), and nanoparticles engineered to transport copper are capable of effectively adjusting copper ion concentrations in lung cancer cells, subsequently inducing cuproptosis as a prospective treatment strategy for lung cancer. Furthermore, our findings suggest that lung cancer cells might counteract the harmful impacts of copper buildup by modulating proteins linked to copper metabolism, bolstering the antioxidant defense mechanisms, altering metabolic pathways, and triggering cellular stress responses and repair mechanisms. Conclusion Cuproptosis represents a novel mechanism dependent on copper that has important implications for the treatment of lung cancer. This process primarily involves the buildup of copper ions, which leads to a disruption in protein homeostasis, ultimately resulting in cell death. Additionally, the abnormal expression of crucial regulatory genes, such as FDX1 and LIPT1, along with transport proteins like CTR1 and ATP7A/B, is closely linked to the advancement of lung cancer. At present, drugs that act as carriers for copper ions (such as elesclomol and disulfiram), metal-organic frameworks based on copper, and copper chelators (including D-penicillamine and ammonium tetrathiomolybdate) have demonstrated promise in eliciting copper-mediated cell death in lung cancer cells. These discoveries suggest new potential targets and strategies for treating lung cancer, which could enhance the prognosis for patients diagnosed with the disease. Graphical abstract